(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2021)
The importance of the research lies in identifying the reality of the skillful performance of female players in the middle Euphrates clubs in futsal football, as well as deriving standards and setting standards for the skillful performance of futsal female players. As for the research problem, through the researchers’ follow-up of most futsal tournaments for female players, they noticed a clear weakness in the skillful performance of this game and without the level of ambition, and this came as a result of selection based on the experience of the training process, and it may be accompanied by randomness in choosing without relying on evaluation evidence that helps in selecting the female athletes, which is what urged researchers to study this phenomenon and stand on its true reality and delve into this matter and find the correct scientific evidence based on the correct scientific foundations for the skills of passing and scoring in futsal football, which is a scientific attempt in order to contribute to the Iraqi feminist sport.